(untitled) (CIPEEX, 2025)
The document details the development of a software system aimed at small medical practices,with the aim of improving the efficiency and organization of daily activities. The suggestedsystem allows healthcare professionals to focus on patient care, integrating essential functionssuch as scheduling appointments, online prescription, managing medical bills and administeringmedical records. The digital platform will facilitate the workflow, reduce errors and improve theorganization of the office. To avoid scheduling conflicts and facilitate automatic appointmentrescheduling and confirmations, the scheduling functionality helps doctors better manage theirschedules. With digital prescription, medications can be prescribed and sent digitally, whichincreases accuracy and speeds up access to medicines. Medical bill management simplifies thepractice’s financial management and automates invoice issuance. Furthermore, the digitalanamnesis form allows a complete and updated record of patient data, which allows for moreindividualized and safer treatment for the patient. The MoSCoW technique will prioritize systemimplementation, ensuring that essential requirements are met before considering otherfunctionalities. Furthermore, the document mentions that to ensure that the system offers acomplete and effective solution for managing small medical practices, subsequent sections willcover details on the system architecture, development, and network structure.